Cystic fibrosis patients of minority race and ethnicity less likely eligible for CFTR modulators based on CFTR genotype - McGarry, Meghan E.; McColley, Susanna A. (Pediatric pulmonology, 2021)
Background Cystic fibrosis transmembrane conductance regulator (CFTR) modulators are disease‐modifying medications for cystic fibrosis (CF) and are shown to be efficacious for only specific CFTR mutations. CFTR mutation frequency varies by ancestry, which is different from but related to demographic racial and ethnic group. Eligibility for CFTR modulator therapy has not been previously reported by race and ethnicity. Methods We conducted a cross‐sectional study of patients in the 2018 CF Foundation Patient Registry. We analyzed the percentage of patients in each US Census defined racial and ethnic group eligible for CFTR modulators based on CFTR mutations approved by the US FDA and then based on both mutations and FDA approval by age. We compared lung function based on CFTR modulator eligibility and prescription. Findings Based on CFTR mutations alone, 92.4% of non‐Hispanic White patients, 69.7% of Black/African American patients, 75.6% of Hispanic patients, and 80.5% of other race patients eligible for CFTR modulators. For each CFTR modulator, Black/African American patients were least likely to have eligible mutations, and non‐Hispanic White patients were most likely. There was no difference in the disparity between racial and/or ethnic groups with the addition of current FDA approval by age. The lowest pulmonary function in the cohort was seen in non‐Hispanic White, Black/African American, and Hispanic patients not eligible for CFTR modulators. Interpretation Patients with CF from minority groups are less likely to be eligible for CFTR modulators. Because people with CF who are racial and ethnic minorities have increased disease severity and earlier mortality, this will further contribute to health disparities.